Philadelphia Battery Service Station booth - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a booth for the Philadelphia Battery Service Station. Batteries of various sizes form part of the display. Some signs read "Philadelphia Diamond Grid Battery."